The ligamentum teres femoris in orangutans. Issue 3 (21st August 2018) - Muchlinski, Magdalena N.; Hammond, Ashley S.; Deane, Andrew S.; Purcell, Maureen; Hemingway, Holden W.; Hantke, Georg; Pastor, Francisco; Garrosa, Manuel; Hartstone‐Rose, Adam
Abstract: Objectives: It is widely viewed that orangutans lack a ligamentum teres femoris (LTF) inserting on the femoral head because orangutans lack a distinct fovea capitis. Orangutans employ acrobatic quadrumanous clambering that requires a high level of hip joint mobility, and the absence of an LTF is believed to be an adaptation to increase hip mobility. However, there are conflicting reports in the literature about whether there may be a different LTF configuration in orangutans, perhaps with a ligament inserting on the femoral neck instead. Here we perform a dissection‐based study of orangutan hip joints, assess the soft tissue and hard tissue correlates of the orangutan LTF, and histologically examination the LTF to evaluate whether it is homologous to that found in other hominoids. Materials and methods: The hip joints from six orangutans were dissected. In the two orangutans with an LTF passing to the femoral head, the LTF was assessed histologically. Skeletonized femora (n=56) in osteological repositories were examined for evidence of a foveal pit. Results: We observed an LTF in two of the three infant orangutans but not in the sub‐adult or adult specimens. Histological examination of the infant LTF shows a distinct artery coursing through the LTF to the head of the femur. One percent of orangutan femora present with a foveal scar, but no pit, on the femoral head. Discussion: Despite being absent in adults, the LTF is present in at least some orangutans during infancy. We suggest that the LTF maintains a role in blood supply to the femoral head early in life. Because the LTF can limit hip mobility, this may explain why the LTF may be lost as an orangutan ages and gains locomotor independence. These findings enhance our understanding of orangutan hip morphology and underscore the need for future soft tissue investigations.